2019
DOI: 10.1021/jacs.9b08960
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced, Metal-Free Carbene Insertion into B–H Bonds between Acylsilanes and Pinacolborane

Abstract: Carbene insertion reactions with B−H bonds are a challenging but promising method for the synthesis of organoboranes. Herein, we report visiblelight-induced B−H insertions of HBpin with acylsilane. This metal-free and operationally simple reaction proceeds in an atom-economical way with broad substrate scope under mild reaction conditions, affording a variety of important α-alkoxyorganoboronate esters in quantitative yields. Control experiments and density functional theory calculations suggest that the siloxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 51 publications
0
47
0
1
Order By: Relevance
“…If the above Norrish reactions took place from the singlet‐excited‐state of the alkanoylsilanes, triplet energy transfer methodology would be a reasonable solution to realize efficient generation of siloxycarbenes. Thus, we decided to develop the generation of siloxycarbenes 2 from alkanoylsilanes 1 through triplet energy transfer and tried to suppress undesired Norrish‐type fragmentations to expand synthetic utility of alkanoylsilanes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the above Norrish reactions took place from the singlet‐excited‐state of the alkanoylsilanes, triplet energy transfer methodology would be a reasonable solution to realize efficient generation of siloxycarbenes. Thus, we decided to develop the generation of siloxycarbenes 2 from alkanoylsilanes 1 through triplet energy transfer and tried to suppress undesired Norrish‐type fragmentations to expand synthetic utility of alkanoylsilanes.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, we have realized the generation of siloxycarbenes from various alkanoylsilanes by visible‐light‐induced energy transfer, and this methodology was successfully applied to C−C coupling reactions with boronic esters or aldehydes. Noteworthy is that Norrish‐type fragmentations of alkanoylsilanes were shown to proceed mainly from singlet‐excited states and these undesired reactions were significantly suppressed by triplet sensitization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The propensity of these species to undergo insertion chemistry has been known since their initial discovery, 46 but was recently exploited by Glorius and coworkers to generate silyl-protected α-boryl alcohols 49 (Scheme 13). 47 The mechanism of the reaction was elucidated by DFT calculations, which showed the formation of an intermediate triplet diradical species (47) that undergoes an α-elimination, followed by a 1,2-silyl shift to afford the corresponding αsiloxycarbene (48). The B-H insertion step was proposed to go through a concerted mechanism based on comparative DFT calculations of the two potential pathways.…”
Section: Siliconmentioning
confidence: 99%
“…As depicted, the yield of 3 i could be enhanced to 82%, when the reaction was carried out in DCM. In addition, we also examined the influences of the wavelengths of the light sources, and the results revealed that the blue LEDs with wavelengths of 425 nm were still the best choice (Table 1, entries [11][12][13][14]. When the reaction was run in more concentrated solution, the yield of 3 i could be enhanced to 85% (Table 1, entry 10).…”
mentioning
confidence: 99%